Blood pressure and risk of headache: a prospective study of 22 685 adults in Norway. Issue 4 (1st April 2002) - Hagen, K; Stovner, L J; Vatten, L; Holmen, J; Zwart, J-A; Bovim, G
Abstract : Objectives: Prevalence studies of the association between blood pressure and headache have shown conflicting results. The aim was to analyse the relation between blood pressure and risk of headache in a prospective study. Methods: A total of 22 685 adults not likely to have headache, had their baseline blood pressure measured in 1984–6, and responded to a headache questionnaire at follow up 11 years later (1995–7). The relative risk of headache (migraine or non-migrainous headache) was estimated in relation to blood pressure at baseline. Results: Those with a systolic blood pressure of 150 mm Hg or higher had 30% lower risk (risk ratio (RR)=0.7, 95% CI 0.6–0.8) of having non-migrainous headache at follow up compared with those with systolic pressure lower than 140 mm Hg. For diastolic blood pressure, the risk of non-migrainous headache decreased with increasing values, and these findings were similar for both sexes, and were not influenced by use of antihypertensive medication. For migraine, there was no clear association with blood pressure. Conclusion: In the first prospective study of blood pressure and the risk of headache, high systolic and diastolic pressures were associated with reduced risk of non-migrainous headache. One possible explanation may be the phenomenon of hypertension associated hypalgesia, which probably involves the baroreflex system influencing nociception in the brain stem or spinal cord.